HOUSE HOLD WATER HANDLING PRACTICE IN SOUTHERN-EAST ETHIOPIA: MAGNITUDE AND ASSOCIATED FACTORS - Deginet Kebede Belihu; Girma Worku Obsie; Melese Tadessa Aredo (International Journal of Public Health Science (IJPHS), 2022)
Household water handling practice is very critical for prevention of water borne communicable disease. This study aimed to assess household water handling practice and associated factors in rural kebeles of Tiyo woreda,  Arsi zone South East Ethiopia.Community-based cross-sectional study was employed among 403 households by using simple random sampling techniques from September 02-25/2019. Data were collected by interviewer administered structured questionnaire, entered into EPI INFO version 7 and analyzed by SPSS Version 20. Logistic regression models were fitted to identify the association between the dependent and independent variables by computing the odds ratios with a 95% confidence intervals at P-value< 0.05. A total of 403 households participated with an overall response rate was 98%. More than fifty percent (53.3%) were found to handle their drinking water properly. Level of education [AOR=3.341,95% CI:(1.536,7.267], monthly income [AOR= 0.291, 95%CI:(0.100,0.848], know about safe water handling [AOR=1.721, 95%CI: (1.103, 2.681], frequency of water collected per day [AOR=3.049, 95%CI: (1.476, 6.299], knowing water treatment [AOR=1.588,95%CI: (1.015,2.485]and methods with draw water from container [AOR=1.840, 95% CI: (1.111, 3.046)] were found to be factors associated with proper water handling practices. Unsafe water handling practiced is high irrespective of the efforts being done the ministry of health and stakeholders were found to be significantly associated in the study area. Thus, Education on water handling practice with emphasis on the consequences of negative impacts of poor water handling practice and implement treating of water at house holds’ level insured good practice.